The Improvement of Mathematics Learning Outcomes on the Flat Shapes Topic Using the PAIKEM Learning Model in Fourth Grade Elementary School Students - Yarem, Naithy; Muhlis; Hety Diana Septika; Sukriadi; Sopyan, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to improve mathematics learning outcomes, particularly in the topic of flat shapes, by using the Active, Innovative, Creative, Effective, and Fun (PAIKEM) learning model for fourth-grade students at SD Negeri 005 Samarinda Seberang. The problem faced was the low mathematics learning outcomes due to unengaging teaching methods and the lack of student participation. This research uses the Classroom Action Research (CAR) method with two cycles of action. Data were collected through observations of teacher and student activities, as well as mathematics learning tests. The results show a significant improvement in student learning outcomes after the implementation of the PAIKEM model. The average learning outcome score in the pre-cycle was 50.8 with a classical completeness rate of 40%, which increased to 70.4 and 52% completeness in Cycle I, and reached an average of 70.8 with a classical completeness of 80% in Cycle II. Student learning activity also improved from an average score of 6.8 in Cycle I to 11.6 in Cycle II. This study concludes that the PAIKEM model is effective in improving mathematics learning outcomes on flat shapes and increasing student participation in mathematics learning. Therefore, it is recommended for teachers to implement this learning model to achieve optimal learning outcomes.